ANALISIS PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH: STUDI LITERATUR - Chindytia; Anak Agung Gede Agung; Komang Heni Cahya Purnami; Ni Luh Gede Chintya Vijayanthi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT School-Based Management (SBM) is an educational management approach that emphasizes school autonomy, participation, transparency, and accountability to improve educational quality. The success of SBM implementation is strongly influenced by principal leadership. This study aims to analyze the role and effectiveness of principal leadership in SBM implementation and identify supporting and inhibiting factors. The study employed a qualitative descriptive approach through a literature review. Data were collected from books, journal articles, and relevant scientific documents and analyzed using content analysis techniques. The findings indicate that principals play a strategic role in planning, organizing, supervising, and empowering school resources. Effective leadership encourages stakeholder participation, strengthens collaboration, improves teacher professionalism, and creates a positive school culture. Supporting factors include leadership competence, teacher commitment, community participation, and a conducive school environment. Meanwhile, limited managerial competence, inadequate resources, financial constraints, and resistance to change remain major challenges. Therefore, effective principal leadership is a key factor in the successful implementation of SBM and the improvement of educational quality. Keywords: Principal Leadership, School-Based Management, Educational Quality